Seismic Local Buckling Limits for Hollow Structural Section and Built-Up Box Columns - Liu, Judy (Engineering Journal, 2024)
Recently completed research on seismic local buckling limits for steel hollow structural section (HSS) and built-up box columns is featured. These National Center for Research on Earthquake Engineering (NCREE) studies are led by Dr. Chung-Che Chou and Dr. Tung-Yu Wu in the Department of Civil Engineering at National Taiwan University (NTU). Dr. Chou also serves as the NCREE Director. Dr. Chou’s research has focused on seismic testing, analysis, and design for steel and post-tensioned self-centering structures. Some recent work includes studies on hybrid simulation of a full-scale steel moment frame, a post-tensioned self-centering brace, novel prediction models for early earthquake warnings, and earthquake reconnaissance work in eastern Taiwan. Dr. Chou’s numerous accolades include the Awards for Excellent Research and Technology Transfers for his leadership on a research team developing a sandwiched buckling-restrained brace and a self-centering brace. Dr. Wu’s research interests include collapse behavior of cold-formed HSS columns under seismic loading, subwavelength seismic metamaterial structures, crack growth in railway crossings under high wheel-rail impacts, and seismic resilience of steel buildings. In addition to multiple scholarships and fellowships, Dr. Wu’s honors include the Raymond C. Reese Research Prize, awarded by the American Society of Civil Engineers (ASCE) for papers representing notable achievements in research with impact on design. The National Science and Technology Council is supporting this research on seismic local buckling limits for HSS and built-up box columns. Selected highlights from both projects are presented, along with a preview of future research tasks.